The Role of Enzymatic Molecular Autopsy for Law Enforcement in Cyanide Poisoning Cases in Rabat, Morocco - Meryem, Karima; Mustafa Yussef (Sriwijaya Journal of Forensic and Medicolegal, 2024)
Introduction: Cyanide poisoning is a serious public health problem throughout the world, including in Morocco. Enzymatic molecular autopsy offers a powerful method for detecting and quantifying cyanide levels in body tissue, which can assist law enforcement in poisoning cases. Methods: This observational study was conducted on 112 research subjects who died from cyanide poisoning in Rabat, Morocco. An enzymatic molecular autopsy was performed to measure cyanide levels in the blood, liver, and brain. Data were analyzed to determine the relationship between cyanide levels and demographic, clinical, and toxicological factors. Results: The highest levels of cyanide are found in the blood, followed by the liver and brain. There is a significant relationship between cyanide levels and causes of death, with cyanide levels highest in suicides and homicides. Conclusion: Enzymatic molecular autopsy should be considered as a routine method in the investigation of cyanide poisoning cases. This can help law enforcement to achieve justice for victims and their families.